2012
DOI: 10.1039/c2dt30383c
|View full text |Cite
|
Sign up to set email alerts
|

The Kubas interaction in M(ii) (M = Ti, V, Cr) hydrazine-based hydrogen storage materials: a DFT study

Abstract: The Cr(II) binding sites of an experimentally realised hydrazine linked hydrogen storage material have been studied computationally using density functional theory. Both the experimentally determined rise in H(2) binding enthalpy upon alteration of the ancillary ligand from bis[(trimethylsilyl)methyl] to hydride, and the number of H(2) molecules per Cr centre, are reproduced reasonably well. Comparison with analogous Ti(II), V(II) and Mn(II) systems suggests that future experiments should focus on the earliest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 43 publications
3
41
1
Order By: Relevance
“…This can be attributed to the transfer of electron density from metal ion to H 2 , which is more profound in going from Sc to Cr. Particularly in Cr-OTPe8H 2 complex; significant decrease in the charge on Cr can be observed due to donation of electron density from metal ion to ligand in accordance with previous report [50]. As a result, amount of charge transferred from H 2 to metal ion in the case of Cr-OTPe8H 2 complex is more than that of other systems.…”
Section: Due To Kubas Interactionsupporting
confidence: 91%
“…This can be attributed to the transfer of electron density from metal ion to H 2 , which is more profound in going from Sc to Cr. Particularly in Cr-OTPe8H 2 complex; significant decrease in the charge on Cr can be observed due to donation of electron density from metal ion to ligand in accordance with previous report [50]. As a result, amount of charge transferred from H 2 to metal ion in the case of Cr-OTPe8H 2 complex is more than that of other systems.…”
Section: Due To Kubas Interactionsupporting
confidence: 91%
“…The isosteric heats of hydrogen adsorption were calculated by tting the adsorption isotherms at 77 K and 87 K into the Clausius-Clapeyron equation (Fig. 23 In this mechanism there are few Kubas sites at room temperature (consistent with the isotherms of these materials at 1 bar) and increasing the pressure deforms the amorphous structure, opening up new Kubas sites as the ligands twist around the metal center. The data for all six materials are shown in Fig.…”
mentioning
confidence: 88%
“…5b Other theoretical computations have shown that titanium decorated nanotubes can adsorb 8 wt% hydrogen, 4 and 12 wt% for Ti decorated polymers, 17 In both cases, each Ti atom was proposed to hold up to 5 hydrogen molecules in a Kubas type interaction. 23 For this reason we have proposed a new model, which has already been shown to be plausible by computational methods. S15 † provides the data for A100-H 2 materials).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is because among all of the potential MXene phases, Ti 2 C has the largest superficial area for every weight. Therefore, it can be considered that Ti 2 C has a relatively high gravimetric hydrogen storage capacity . Equation can be used to calculate E b (the bond energy) between H 2 and the host material Ti 2 C: trueEb=(Ehost+n0.166667emEnormalH2-Ehost+n0.166667emnormalH2)n …”
Section: Energy Storagementioning
confidence: 99%